ANALISIS ENDORSE ATTRACTIVENESS DAN CONTENT AESTHETIC QUALITY TERHADAP BRAND LOYALTY DAN BRAND LOVE DENGAN CUSTOMER ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Survey Pada Pengguna Skincare Avoskin di Kota Semarang) - Devismara, Aura Bunga; Lumban Batu, Kardison; Aryandika, Ardiaz Ajie (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The growing development of local skincare brands makes competition increasingly competitive. One of the marketing trends in 2023 is using influencer marketing. In the beauty industry, influencer services are often used. Apart from this trend, research inconsistencies were found between the attractiveness of endorsements and brand loyalty carried out in previous research. Therefore, on the basis of trends and images between the attraction of support and brand loyalty. This research aims to analyze the influence of the aesthetic quality of content and endorser attractiveness on brand love and brand loyalty, by considering the role of customer involvement as an intervening variable. The concept of the research framework model developed between support attractiveness, aesthetic quality of content, affection preferences, cognitive processing, brand loyalty and brand love comes from research that has been conducted. The theory used in this research is selfconformity theory. This research used a purposive sampling technique with a sample size of 220 respondents. The method used in this research is SEM (Structural Equation Modeling) using the AMOS 24 program. The findings in this research succeeded in proving that cognitive processes can strengthen the relationship between the attractiveness of endorsements and the aesthetic quality of content on brand loyalty by having a significant positive influence. Endorsement attractiveness has a positive and significant effect on cognitive processing variables and affection preferences. Affection preferences were unable to have a significant and positive effect on the brand love variable. However, there is a non-significant rejection of the hypothesis: the aesthetic quality of other content has a positive and insignificant effect on the variables cognitive processing and affection preferences, cognitive processing has a positive and insignificant effect on the variables brand loyalty and brand love, affection preferences has a negative and insignificant effect on brand loyalty variable.